Perceptual interactions among food odors: Major influences on odor intensity evidenced with a set of 222 binary mixtures of key odorants - Ma, Yue; Tang, Ke; Xu, Yan; Thomas-Danguin, Thierry (Food chemistry, 2021)
•Intensity of binary odor mixtures of food odorants is shaped by perceptual interactions.•In most cases, the odor intensity of binary mixtures is close to the stronger component.•In almost all cases, the components’ odors could be perceived within the mixture.•Odor masking occurred more frequently when pleasantness was different between the components.•Statistically significant synergy was observed in less than 1% of cases. This study explored the impact of perceptual interactions on the odor intensity of 222 binary mixtures designed from 72 odorants found in food products. Odor intensity was rated by 30 trained subjects. The results showed that in most cases, the components’ odor was perceived within the mixture and their intensity remained the same as in the unmixed situation in 54.3% of cases. Masking was the second major effect (44.8%) and occurred more frequently when components’ pleasantness was significantly different. Synergy occurred in a small number of cases (0.9%) and only for four compounds. The overall odor intensity of the mixture was determined to be equal to the strongest component in most cases (73.9%), while partial addition was observed as the second most frequent effect (21.7%), especially when the components had equal intensity. Overall, this work provides general rules about the outcome to expect when mixing key components of food aromas.